Harnessing the Activation of RIG-I Like Receptors to Inhibit Glioblastoma Tumorigenesis - Bufalieri, Francesca; Basili, Irene; Di Marcotullio, Lucia; Infante, Paola (Frontiers in Molecular Neuroscience, 2021)
Glioblastoma (GB) is an incurable form of brain malignancy in adult with a median survival of less than 15 months. Current standard of care, which consists of surgical resection, radiotherapy and chemotherapy with temozolomide, has been unsuccessful also due to an extensive inter- and intra-tumoral genetic and molecular heterogeneity. This aspect represents a serious obstacle for developing of alternative therapeutic options for GB. In the last years, immunotherapy has emerged as effective treatment for a wide range of cancers and several trials have evaluated its effects in GB patients. Unfortunately, clinical outcomes were disappointing particularly because of the presence of tumor immunosuppressive microenvironment. Recently, anti-cancer approaches aimed to improve the expression and the activity of RIG-I like receptors (RLRs) have emerged. These innovative therapeutic strategies attempt to stimulate both innate and adaptive immune responses against tumor antigens and to promote the apoptosis of cancer cells. Indeed, RLRs are important mediators of innate immune system by triggering the type I interferon (IFN) response upon recognition of immunostimulatory RNAs. In this mini-review, we discuss the functions of RLRs family members in the control of immune response and we focus on the potential clinical application of RLRs agonists as a promising strategy for GB therapy.